Thank you Sjaastad (1928-2022) for everything we learned from you - Silva-Néto, Raimundo Pereira; Valença, Marcelo Moraes (Headache Medicine, 2022)
Editorial Thank you Sjaastad (1928-2022) for everything we learned from you